ThinkMeal: Ingredient Classification and Recipe Recommendation Application - Aungtanagul, Napat; Hoontamai, Thitiwut; Chotiphan, Theerada; Chotipant, Supannada (My University, 2024)
Food is one of the four essential factors, and nowadays, Thai cuisine is highly famous domestically and internationally. The majority of Thai culinary culture involves preparing and enjoying meals within households. Therefore, it's essential to have recipes that are easily accessible and adjustable to one's taste preferences. Currently, there are applications available to assist in finding recipes. However, these applications typically limit searches to recipe or ingredient names. To address this limitation, a new application called "ThinkMeal"has been developed to recommend dishes based on available ingredients. ThinkMeal utilizes a model based on the MobileNetV2 image classification, achieving an impressive accuracy of up to 95.14% in experiments conducted with 13 types of ingredients. This enables users to conveniently find recipes that meet their preferences, either by searching recipe names and ingredient names or even by uploading images of available ingredients. This application serves as a helpful tool for individuals interested in cooking, offering convenient assistance in meal preparation.
Keywords: Ingredient Image Classification; Mobile Application; Thai Recipe Recommendation